Electrospun Ta-doped TiO2/C nanofibers as a high-capacity and long-cycling anode material for Li-ion and K-ion batteries. Issue 39 (2nd October 2020) - Su, Die; Liu, Li; Liu, Zhixiao; Dai, Jing; Wen, Jiaxing; Yang, Min; Jamil, Sidra; Deng, Huiqiu; Cao, Guozhong; Wang, Xianyou
Abstract : Ta-doped TiO2 /C nanofibers can enhance the electrical conductivity, shorten the ion transport distance. Thus it shows outstanding electrochemical performance in both Li/K-metal half cells and Li/K full cells.. Abstract : Ta-doped TiO2 /C nanofibers are synthesized by an electrospinning method. First-principles calculations reveal that the Ta dopant can lower the Li/K diffusion barrier, which is beneficial for improving the rate capability. According to the electronic structure analysis, the dopant can obviously shift the conduction band of TiO2 downward, resulting in significantly improved electronic conductivity. Ta doping causes phase transformation from anatase to rutile, and increases the specific surface area. The well-designed rutile Ta-doped TiO2 /C nanofibers show outstanding electrochemical properties in both Li-metal half cells and K-metal half cells, which are much better than those of pristine anatase TiO2 /C nanofibers. At 2 A g −1, 5% rutile Ta-doped TiO2 /C nanofibers could deliver high reversible specific capacities of 399 mA h g −1 in Li-ion batteries after 1000 cycles whereas deliver 148 mA h g −1 in K-ion batteries after 800 cycles. When assembled, the full cells with 5% rutile Ta-doped TiO2 /C nanofibers as the anode and commercial LiFePO4 /perylene-3, 4, 9, 10-tetracarboxylic dianhydride as the cathode show excellent cycling performance and can light up more than 18 LEDs. These results demonstrate that Ta-doped TiO2 /C nanofibers are a promising anode material for Li/K ion batteries.